Microfluidic shear‐induced conformational transition and crystallization of P3HT in toluene. Issue 2 (11th November 2019) - Liu, Ying; Hu, Shan; Liu, Fengquan; Wei, Nan; Zhou, Jianjun; Li, Lin; Huo, Hong
Abstract: Very few studies have reported a shear‐induced conformational transition and formation of a flow‐induced precursor (FIP) of conjugated polymers in solution. In this work, a microfluidic shear system was used to apply shear on poly(3‐hexylthiophene) (P3HT) in toluene. The ultraviolet‐visible spectrum verifies that microfluidic shear can induce the coil‐to‐rod transition of P3HT in a dilute toluene solution. When the concentration of rod‐like segments is above a certain threshold, interchain π‐π stacking of the rods spontaneously happens in the sheared solution. Studying the isothermal crystallization of P3HT at 16°C in the sheared solution shows that crystallization occurs after some relaxation of the π‐π stacking of the rods, suggesting that the π‐π stacked rods are not the nuclei or crystals of P3HT and thereby verifying that shear‐induced π‐π stacked rods are mesomorphic; namely, they are FIPs. Shear temperature is an important parameter for determining the amount of FIP. The amount of FIP dramatically affects the crystallization kinetics, dispersion, amount, and intrachain ordering of P3HT nanofiber when P3HT isothermally crystallized at 12°C in toluene. Abstract : Microfluidic shear can induce the coil‐to‐rod transition and interchain π‐π stacking of the rods of poly(3‐hexylthiophene) (P3HT) in toluene. It is verified that shear‐induced π‐π stacked rods are mesomorphic, namely, flow‐induced precursors (FIPs). Shear temperature is an important parameter for determining the amount of FIP. The amount of FIP dramatically affects the crystallization kinetics, dispersion, amount, and intrachain ordering of P3HT nanofiber when P3HT is isothermally crystallized at 12°C in toluene.